A study of q-Lagranges polynomials of three variables - Khan, Mumtaz Ahmad; Rahman Khan, Abdul (Pro Mathematica, 2004)
The present paper introduces a q-analogue of Lagranges polynomials of three variables due to Khan and Shukla and gives certain results involving these polynomials.